The Effectiveness of Using the Quizizz Application in Kanji Learning for Students of the Japanese Language Education Study Program, Faculty of Teacher Training and Education, University of Riau - Diandra, Nanda; Nana Rahayu; Sri Wahyu Widiati (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is an experimental study using a pre-experimental method with a One-Group Pretest-Posttest design, aimed at determining the effectiveness of using the Quizizz application in Kanji learning for students of the 2022 cohort of the Japanese Language Education Study Program, Faculty of Teacher Training and Education, University of Riau. This design involves only one experimental group and does not include a comparison group. The subjects of this study were 36 students from the 2022 cohort of the Japanese Language Education Study Program. Data collection was carried out using tests. The research instruments used were the Quizizz application and test items measuring learning outcomes. The results of data analysis showed that the average score before the treatment was 48.61, and the average score after the treatment was 78.72. The results of the Paired Sample T-test showed a Sig. (2-tailed) value of 0.000. Based on the results of the paired sample t-test, it can be concluded that the use of the Quizizz application in Kanji learning is effective.